种翅片式换热器专用耐高温腐蚀柔性涂料的制备方法 (2019)
本发明公布了种翅片式换热器专用耐高温腐蚀柔性涂料的制备方法，其主要特征是公开种耐高温腐蚀柔性涂料的配方(以重量计)：树脂33～80，填料50～10，硅纳米聚合物5～20，溶剂5～8，阻凝剂1～10，固化剂1～3、促进剂0.5～3。其中还公布了硅纳米聚合物的制备方法，施工工艺如下：翅片管先进行表面处理，然后喷涂该涂料，加热固化，在翅片管表面形成层均匀的耐高温腐蚀的柔性涂层，可以取代搪瓷涂层，应用于180～220℃条件的发电厂、炼钢厂、石化、硫酸行业的换热设备、低温湿煤气加热器、烟气余热回收等，具有广阔的应用前景。加工成的样品如附图照片。 The invention discloses a preparation method of a high-temperature corrosion resisting flexible paint special for a finned heat exchanger. The preparation method is mainly characterized by being prepared from, by weight, 33-80 parts of resin, 50-10 parts of filler, 5-20 parts of a silicon nano-polymer, 5-8 parts of a solvent, 1-10 parts of an anti-coagulant, 1-3 parts of a curing agent and 0.5-3 parts of an accelerant. The invention further discloses a preparation method of the silicon nano-polymer. The construction process includes the following steps that finned tubes are subjected to surface treatment, then the paint is sprayed, heating is performed for curing, and a uniform high-temperature corrosion resisting flexible coating is formed on